An evaluation of factors of permanent central crown fractures in 7-12 years old children - Ghandehary- Motlagh M. Assistant Professor; Farajy P. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: Central crown fractures of deciduous and permanent teeth lead to unfavorable"npsychological effects on both children and their parents. Moreover, it can cause malocclusion. So,"nrecognizing tooth fracture reasons plays an important role to prevent its side effects."nAim: The aim of this study was to investigate the reasons' of permanent central crown fractures in (7-12)"nyears old children."nMaterials and Methods: Records of 218 children, with at least one central tooth fracture, referred to"npediatric department of faculty of dentistry of Tehran University of Medical Sciences, from 1999 to"n2000, were studied. All the related information about fracture such as: reason, location, time, type of"nocclusion, and type of fracture were recorded."nResults: It was found that falling down (45.4%) and having contact with external objects (21.6%) were"nthe main reasons for permanent centrals fractures. The mean age of these children was 9.78±1.24 and"n63.3% of them were boys. It should be noted that 41.3% of them had unsupported lip. The highest rate of"nfractures belonged to upper centrals. Based on Ellis classification, most fractures were of degree 3"n(52.7%). There was no significant relationship between overbite and overjet with the degree of fracture"n(P<0.05)."nConclusion: Dental skeletal malocclusions such as CI II, Div I, central incisors protrusion and"ndevelopmental defects of tooth structure should be considered as determinant factors in tooth crown"nfractures.